1999
DOI: 10.1046/j.1432-1327.1999.00580.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative promoters direct tissue‐specific expression of the mouse protein phosphatase 2Cβ gene

Abstract: Type 2C protein phosphatases (PP2Cs), a class of ubiquitous and evolutionally conserved serine/threonine protein phosphatases, are encoded in at least four distinct genes and implicated in the regulation of various cellular functions. Of these four PP2C genes, the expression of the PP2Cb gene has been reported to be tissue-specific and development-dependent. To understand more precisely the regulatory mechanism of this expression, we have isolated and characterized overlapping mouse genomic l clones. A compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Analysis of PP2CP transcripts showed that exon-1 transcripts were expressed ubiquitously in several tissues, whereas exon-2 transcripts were predominantly expressed in the testis, intestine and liver. These results suggested that the alternative usage of two promoters within the PP2CP gene regulates tissue-specific expression of PP2CP mRNA (Ohnishi et al, 1999).…”
Section: Protein Phosphatase 2cmentioning
confidence: 86%
“…Analysis of PP2CP transcripts showed that exon-1 transcripts were expressed ubiquitously in several tissues, whereas exon-2 transcripts were predominantly expressed in the testis, intestine and liver. These results suggested that the alternative usage of two promoters within the PP2CP gene regulates tissue-specific expression of PP2CP mRNA (Ohnishi et al, 1999).…”
Section: Protein Phosphatase 2cmentioning
confidence: 86%
“…As PP2C exists as multiple isoforms this allows for tissue specific expression (53). PP2C isoforms are broadly expressed but most abundant in heart and skeletal muscle (54). PP2C is insensitive to okadaic acid and other naturally-occurring protein phosphatase inhibitors and the lack of pharmacological agents able to modulate PP2C activity has hindered the understanding of its character in regulating cell function.…”
Section: Pp2cmentioning
confidence: 99%
“…There are several precedents in the literature to support this, Van den Wijngaard et al (14) described two promoters involved in the transcriptional regulation of the human BMP-4 gene, one upstream of exon 1, the second located in intron 1, upstream of exon 2, giving rise to different transcripts in a cell type and differentiation-dependent manner. In another example, Ohnishi et al (15) isolated a type 2C protein phosphatase (PP2Cbeta) with different 5Ј termini. Subsequent analysis of the 5Ј flanking regions of exon 1 and 2 by reporter gene showed that these regions acted as distinct promoters.…”
Section: Fig 2-continuedmentioning
confidence: 99%
“…Subsequent analysis of the 5Ј flanking regions of exon 1 and 2 by reporter gene showed that these regions acted as distinct promoters. Analysis of PP2Cbeta transcripts by RT-PCR showed that exon-1 and exon-2 derived transcripts were differentially expressed, suggesting that alternative promoter usage regulated tissue-specific expression of PP2Cbeta (15).…”
Section: Fig 2-continuedmentioning
confidence: 99%